A New Phenolic Compound from the Roots of Flue-Cured Tobacco and Its Anti-Tobacco Mosaic Virus Activity - Xu, Wenxiu; Han, Yi; Zhang, Xia; Chen, Zhangyu; Yang, Guangyu; Guo, Yadong; Chen, Yongkuan (Asian Journal of Chemistry, 2014)
A new phenolic compound, (6S)-6-(4-(hydroxymethyl)-2-methoxyphenyl)-6-methoxy-2-methylheptan-1-ol (1), was isolated from the roots of flue-cured tobacco (a variety of Nicotiana tabacum L). Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was tested for its anti-tobacco mosaic virus (anti-TMV) activity and it shows potential anti-tobacco mosaic virus activity with inhibition rates of 16.4 %.